Proyecto Intangible: diez años de arte, activismo y comunicación por la defensa del patrimonio cultural en la costa norte del Perú - Orrillo Puga, José Carlos (2025)
In recent decades, cultural heritage has been the scene of multiple tensions in Latin America: processes of accelerated destruction, fragmented or nonexistent institutional policies, and limited coordination with local communities. In contexts marked by exclusion, neglect, and a lack of cultural identity, heritage becomes a field of symbolic, political, and community disputes. This article proposes to address one of these disputes through the experience of the Intangible project, an art, activism, and communication project developed since 2015 in the Quebrada Santo Domingo archaeological site on the northern coast of Peru. In this place, where a valuable set of pre-Hispanic vestiges threatened by agricultural invasions and urban expansion survive, Intangible has led a persistent campaign to defend, appropriate, and conserve heritage, engaging schoolchildren and residents to recover and redefine the presence of the Triple Spiral geoglyph in the collective imagination.